Determinants of Economic Growth in Syria between 1980 and 2010 - Mohsen, Adel Shakeeb; Chua, Soo Y.; Che Sab, Che Normee (2017)
This study attempts to investigate the determinants of economic growth in Syria from 1980 to 2010. Results from the Johansen cointegration test indicate that public sector investment, private sector investment, exports, oil price, and population growth have positive long-run relationships with economic growth. Public sector investment has the biggest effect on economic growth. The Granger causality test results indicate bidirectional causality relationships between public sector investment, private sector investment, oil price, population growth and GDP in the short and long run. There are also bidirectional causality relationships between exports and GDP in the short run, and unidirectional causality relationship running from exports to GDP in the long run.